GIVING OF LIME AND HONEY MASKS TO ADOLESCENT WOMEN WITH ACNE VULGARIS DURING MENSTRUATION AT THE HURUN INN PETERONGAN JOMBANG HOSTEL: A CASE STUDY - Siti Roudhotul Jannah; Muzayyaroh Muzayyaroh; Syafira Ayu Nurellia Fajrin; Good Nur Abidah (International Journal of Social Science, 2021)
Acne vulgaris occurs due to clogged pores resulting in thickening of the skin at the opening of the holes which occurs due to increased oil production in the oil glands (sebaceous glands). The cause of acne in young women is because they often eat oily foods such as fried foods and lack of rest due to school and dormitory activities which can trigger acne. (Suryoprajogo, Nadine: 2012).The purpose of this study was to provide midwifery care to young women Ms. "A" with acne vulgaris during menstruation by giving a mask of lime and honey which is applied evenly to the face for 30 minutes.The method used in this research is qualitative research with a case study approach. The focus of this case study is Young Women Ms. “A”. The location of the research was carried out at the Hurun Inn Peterongan Jombang Dormitory. Data collection techniques using interviews and observation and documentation.The results of Midwifery Care that had been given to the young woman Ms "A" with acne during menstruation did not find data indicating abnormalities. Care Plans can be implemented in this Midwifery Care. The final evaluation found that the young woman Ms "A" was running smoothly without any problems and there were no complications. In the management of Midwifery Care, there is no gap between theory and cases that occur.The conclusion of the process of healing / preventing acne in young women Ms "A" with acne during menstruation went according to plan with a final evaluation after 14 days carried out without problems/complications.